Ma and Sun on Insider Trading Ethics - Snoeyenbos, Milton (Journal of business ethics, 2000)
Ma and Sun have recently argued that some forms of insider trading are ethically acceptable. We argue that the authors fail to prove three key premises of their argument, which is therefore unsound.